Impact of Techno Overload Work Performance and Work Engagement as Intervening Variables in Semarang City SMEs - Lelani, Siska; Haqq, Zulkifli Nurul; Firdaus, Firdaus (Jurnal Manajerial, 2024)
Background – Stress caused by technology overload in the workplace is one of the main factors leading to workplace stress as well as the demand for continuous improvement in work performance which can eventually lead to feelings of pressure and work overload. Aim - This study is to analyze the impact of Techno-Overload on Work Performance with Work Engagement as an Intervening Variable on MSME Workforce in Semarang City. Design / methodology / approach – The method used in this research is survey methodology and respondents in the SMEs workforce in Semarang, Central Java, Indonesia. SMEs in the Food & Beverage, Handicrafts, Fashion/Clothing, Retail/Minimarket, Services, and Other sectors were sampled because the workforce requires technostress-related treatment related to the types of disorders in the workforce and organizational losses, such as fatigue, dissatisfaction, anxiety, and decreased productivity. To achieve the objectives of this study, researchers involved 315 workers from 6 sectors and distributed them to SMEs in Semarang City. Findings – The results of this study techno-overload as a technostress variable have a positive relationship to work performance. However, this study shows that work engagement has a significant influence in influencing work performance but the role of work engagement has no influence in mediating technological overload on work performance. This research is to provide an understanding of technostress that has a negative impact on MSMEs so that the workforce is able to take steps to overcome it and theoretically this research can be a benefit for further research. Conclusion - Low techno-overload in SMEs in Semarang City can improve workforce performance. The higher work engagement and the lower techno- overload in the workforce of SMEs in Semarang City can improve workforce performance Research implication – This research is to provide an understanding of technostress that has a negative impact on SMEs so that the workforce is able to take steps to overcome it and theoretically this research can be a benefit for further research. Limitations - This research solely concentrates on one primary stress variable, techno-overload, because this variable significantly affects workers within the research context. There are still many research variables that could be explored regarding the phenomenon of technostress affecting job performance. Another limitation of this study is that the researchers only conducted the study in one city.